The CO sub(2) tracer clock for the Tropical Tropopause Layer - Park, S; Jimenez, R; Daube, B C; Pfister, L; Conway, T J; Gottlieb, E W; Chow, VY; Curran, D J; Matross, D M; Bright, A; Atlas, EL; Bui, T P; et al. (Atmospheric chemistry and physics discussions, 2007)
Observations of CO sub(2) were made in the upper troposphere and lower stratosphere in the deep tropics in order to determine the patterns of large-scale vertical transport and age of air in the Tropical Tropopause Layer (TTL). Flights aboard the NASA WB-57F aircraft over Central America and adjacent ocean areas took place in January and February, 2004 (Pre-AURA Validation Experiment, Pre-AVE) and 2006 (Costa Rice AVE, CR-AVE), and for the same flight dates of 2006, aboard the Proteus aircraft from the surface to 15 km over Darwin, Australia (Tropical Warm Pool International Cloud Experiment , TWP-ICE). The data demonstrate that the TTL is composed of two layers with distinctive features: (1) the lower TTL, 350-360 K (potential temperature ([thetas]); approximately 12-14 km), is subject to inputs of convective outflows, as indicated by layers of variable CO sub(2) concentrations, with air parcels of zero age distributed throughout the layer; (2) the upper TTL, from [thetas]= ~360 K to ~390 K (14-18 km), ascends slowly and ages uniformly, as shown by a linear decline in CO sub(2) mixing ratio tightly correlated with altitude, associated with increasing age. This division is confirmed by ensemble trajectory analysis. The CO sub(2) concentration at the level of 360 K was 380.0( plus or minus 0.2) ppmv, indistinguishable from surface site values in the Intertropical Convergence Zone (ITCZ) for the flight dates. Values declined with altitude to 379.2( plus or minus 0.2) ppmv at 390 K, implying that air in the upper TTL monotonically ages while ascending. In combination with the winter slope of the CO sub(2) seasonal cycle (+10.8 plus or minus 0.4 ppmv/yr), the vertical gradient of 0.78 ( plus or minus 0.09) ppmv gives a mean age of 26( plus or minus 3) days for the air at 390 K and a mean ascent rate of 1.5( plus or minus 0.3) mm s super(− 1). The TTL near 360 K in the Southern Hemisphere over Australia is very close in CO sub(2) composition to the TTL in the Northern Hemisphere over Costa Rica, with strong contrasts emerging at lower altitudes (<360 K). Both Pre-AVE and CR-AVE CO sub(2) observed unexpected input from deep convection over Amazonia deep into the TTL. The CO sub(2) data confirm the operation of a highly accurate tracer clock in the TTL that provides a direct measure of the ascent rate of the TTL and of the age of air entering the stratosphere.